TASK-BASED LEARNING TEACHING METHOD IN ENHANCING STUDENTS’ SPEAKING SKILL AT POLITEKNIK UNGGUL LP3M MEDAN - Hermansyah, Hermansyah (JURNAL ILMU PENDIDIKAN, 2024)
The objectives of the study were to determine the process and the result of students’ increasing English speaking ability at Politeknik Unggul LP3M Medan. This study used qualitative and quantitative approaches through task-based learning. The research methodology used is an action-research developed by Cohen et al., 2018 with the spiral model by phases: planning, action, observation, and reflection. The population of the research was the 3rd semester students of Accountancy study program in academic year 2023/2024. There were 60 students of 2 classes involved in the study. Data collection techniques in this study conducted by observation, field note of the researcher/collaborator, and photos as documentation. Meanwhile, for quantitative data is gathered by test (the pre-test, the evaluation of group discussions cycle 1, cycle 2, and cycle 3, and the post-test). The results showed that there was a significant increase in the ability of students in speaking English after attending the subject of speaking II in semester III through task-based learning. Based on the test results of students English speaking ability of the three aspects assessed: accuracy, fluency, and pronunciation showed that the pre-test average student score = 17%, cycle 1 = 20%, cycle 2 = 67%, cycle 3 = 81% and post-test = 84%. Therefore, the study concluded that the students' speaking ability at Politeknik Unggul LP3M can be enhanced through task-based learning approach.